BREEDING FOR BETTER GROWTH OF Calliandra calothyrsus Meissn., A FAST GROWING LEGUME FOR WOOD-ENERGY - Rina Laksmi Hendrati; Siti Husna Nurrohmah (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2019)
Short-rotation woody crops for renewable energy in anticipating decreasing fossil energy resources, has been a great interest for tropical countries where rain and sunshine are abundant. Calliandra calothyrsus, a multipurpose tree suitable for energy-wood is a very potential as short-rotation crop. This nitrogen-fixing species can be utilized as energy-wood by planting once but is able to secure annual harvest up to 15-20 years from its coppices. Beside that, this species supports earth vegetation cover for mitigating climate change. This fast growing, high volume and quality species fulfills requirement for energy needs as renewable wood biomass. In optimizing this role, its genetic improvement was undertaken during 2011 - 2014 to obtain the best energy-wood individuals in volume and quality. This study examined the growth-gain by comparing off spring of genetically improved trees (5 families) selected in 2014 from progeny test in Wonogiri, Central Java, to five (5) families from the unimproved ones. Significant differences on important growth characters have been obtained at the age of 4-month plants ready for field plantation. Calliandra’s genetic improvement has proven to increase the number of leaves, height, diameter and seedling quality up to 23.4 percent, 24.3 percent, 6.7 percent and 20 percent consecutively. More complete materials have been established as realized genetic-gain trials in 2016. It is expected that similar trends will be realized in the fields.